Study on Student’s Perception on The Knowledge and Usage of Air Conditioning from the Electricity Aspect - Abdullah, Nurul Hidayah Liew; Roslan, Fathurrahman (Research and Innovation in Technical and Vocational Education and Training, 2022)
Nowadays, air conditioning is widely used, especially in tropical and hot climates countries, including Malaysia. Thus, has increase on demand for air conditioning needed, it results that problems occur uncontrolled and excessive usage of air conditioning that leads to an increase in electricity costs. Therefore, this study was conducted to identify the perceptions of Air Conditioning and Refrigeration (BBG), Faculty of Technical and Vocational Education (FPTV), Universiti Tun Hussein Onn Malaysia (UTHM) students on the knowledge and usage of air conditioning from the aspect of electricity. This research is conducted in the form of a quantitative methods survey using a questionnaire as instrument for collecting data. Sample data from 63 students in years 3 and 4 BBG program, FPTV, UTHM using simple random selection. Data were analyzed using mean, standard deviation, and Pearson correlation. The results showed that the BBG, FPTV students’ perception on knowledge and usage of air conditioning in terms of electricity is high. Furthermore, the results of the study also show that there is a strong and significant relationship between the perceptions of BBG, FPTV students on the knowledge and use of air conditioning from the aspect of electricity. In conclusion, the integration of knowledge and air conditioning use must be considered in order to effectively manage daily energy production and provide benefit to all users.